2015
DOI: 10.1097/mbp.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Is white-coat hypertension a risk factor for carotid atherosclerosis? A review and meta-analysis

Abstract: The association of white-coat hypertension (WCH) with target organ damage is still debated; in particular, the relationship of this blood pressure phenotype with subclinical vascular damage remains controversial. Thus, we carried out a systematic review and meta-analysis to provide updated information on carotid structural changes in WCH. Studies were identified using the following search terms: 'white coat hypertension', 'isolated clinic hypertension', 'carotid artery', 'carotid atherosclerosis', 'carotid int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…This may lead to an increase in negative health outcomes over time. A recent meta-analysis of 10 studies reported that carotid atherosclerosis was significantly increased in patients with WCH compared with normotensive individuals [38]. In addition, although we did not detect a significant difference, one meta-analysis reported a significant increase in LV mass in patients with WCH compared with those with normal BP [1].…”
Section: Discussionmentioning
confidence: 88%
“…This may lead to an increase in negative health outcomes over time. A recent meta-analysis of 10 studies reported that carotid atherosclerosis was significantly increased in patients with WCH compared with normotensive individuals [38]. In addition, although we did not detect a significant difference, one meta-analysis reported a significant increase in LV mass in patients with WCH compared with those with normal BP [1].…”
Section: Discussionmentioning
confidence: 88%
“…It appears from the present study that in WCH office BP predicts, together with other factors, long-term outcome and that its elevation contributes to the increased risk of cardiovascular events 15 as well as to the higher prevalence of subclinical cardiac and vascular damage reported for this condition in several studies. 13,[19][20][21]26,27,36,37 The following additional points deserve mention. One, compared with individuals in whom WCH was unstable, stable WCH was characterized by an older age, a greater body mass index, an increased left ventricular mass, and higher serum cholesterol and glucose values.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] This is because although in several studies and meta-analyses WCH has been reported to have a cardiovascular risk similar or not significantly greater than that of normotensive individuals, [6][7][8][9][10][11][12] in other studies the risk of this condition in untreated or treated patients has been found to be less than that of true hypertensive but greater than that of normotensive individuals. [13][14][15][16][17][18] Individual studies and meta-analyses have also reported that compared with normotensive controls subjects with WCH exhibit (1) a higher prevalence of overweight or obesity, dyslipidemias, diabetes mellitus, or an impaired fasting plasma glucose state than normotensive controls, 1 (2) a greater prevalence of asymptomatic organ damage [19][20][21] with documented prognostic significance, [22][23][24][25] and (3) an increased risk of developing true hypertension or diabetes mellitus. 26,27 Stratifying cardiovascular risk within the WCH categories is of obvious clinical importance because higher risk levels may justify the decision to adopt a closer follow-up as well as to start antihypertensive drug treatment.…”
mentioning
confidence: 99%
“…We ourselves have recently performed a systematic review and meta‐analysis in order to provide updated information on carotid structural changes in WCH . A total of 3478 untreated patients (940 normotensive [48% men], 666 WCH [48% men], and 1872 hypertensive individuals [57% men]) from 10 studies were analyzed.…”
mentioning
confidence: 99%